THE DEVELOPMENT OF A MULTI-ETHNIC AND MULTI-RELIGIOUS SOCIETY IN MALAYSIA - Raja Sulong, Raja Hisyamuddin; Abd Rahman, Mohamad Zaidi; Hussain, Amjad M. (Journal of Al-Tamaddun, 2019)
Malaysia has its own uniqueness with its population consists of multiple races and religions. The presence of this multi-ethnic and multi-religious society is caused by various factors that related to human life such as jobs security, national policy and so on. This article will attempt to examine the factors of the Malaysia’s demographic changes and development which will cover three phases i.e. the Pre-colonial period, the Colonial period and Post-colonial period. It also discusses the historical facts of a multi-ethnic and a multi-religious society in Malaysia. In order to examine the subject matter, library research has been conducted to seek the data needed. Numerous historical literature related to this study have been reviewed. This study shows that the development of multi-ethnic and multi-religious society in Malaysia was caused by several factors such as migration and colonization. These factors triggered demographic changes in Malaysia’s population which can still be noticed as one of the unique features of the state until today.